A novel homozygous mutation in the SLCO2A1 gene causing pachydermoperiostosis: Efficacy of hydroxychloroquine treatment. Issue 5 (21st April 2018) - Alessandrella, Annalisa; Della Casa, Roberto; Alessio, Maria; Puente Prieto, Jorge; Strisciuglio, Pietro; Melis, Daniela
Abstract : Pachydermoperiostosis (PDP), otherwise known as primary hypertrophic osteoarthropathy, is characterized by digital clubbing, pachydermia and subperiosteal new bone formation. Joint pain, polyarthritis, cutis verticis gyrata, seborrhea, and hyperhidrosis are frequently associated to this condition. We report a 17‐year‐old boy presented with pain and swelling of knees and ankles, and progressive thickening of skin face with seborrhea from about 4 years. At the admission he also showed digital clubbing of both hands and feet and palmoplantar hyperhidrosis. We hypothesized PDP and molecular analysis confirmed diagnosis showing a novel mutation in a homozygous state in the SLCO2A1 gene coding for prostaglandin transporter. He started therapy with hydroxychloroquine with a great improvement in joint pain and skin conditions. This is the first reported case of PDP who was successfully treated with hydroxychloroquine, with effects not only on arthralgia but also, surprisingly, on skin conditions.